Caracterização das áreas de pesca artesanal de lagosta na Praia da Redonda, Icapuí - Ce - Almeida, Lorena Galletti de (2010)
The lack of studies about artisanal fisheries difficult and often prevents the solution of their problems. Researches aiming at enhancing and documenting the knowledge about this kind of fisheries are of great importance for the maintenance and survival of communities engaged in artisanal fishing. The main objective of this study was to characterize the fishing grounds traditionally used by artisanal fishermen of Redonda‟ beach, Icapuí – CE, to catch lobster, in an attempt to provide tools for structuring and promoting instruments aimed at improving the fishing in this community. The main fishing sites traditionally used by artisanal fishermen were georeferenced by boat trips led by experienced fishermen of the community and with the use of GPS. The main fishing areas were delimited with the support of a Nautical Chart. Bathymetric and sedimentological data of the continental shelf adjacent to Redonda‟s beach were acquired to create thematic maps. The total production of whole lobster was obtained by monitoring 18 barracões. The fishing landing of twenty boats was monitored along three months. 104 questionnaires were applied to the artisanal fishermen in an attempt to assess the traditional knowledge in relation to fishing areas. Finally, was obtained oceanographic and environmental data that influence the fishing activity at Redonda‟s beach. In total, 114 fishing sites were mapped and eight main areas where fishermen catch lobster were delimited: Restinga, Buraco, Bugalhal, Cabeço, Banco, Molhe, Fundo and Risca. These areas are within a "fishing zone" known as the Sea of Redonda. With the exception of the fishing area called Risca, which is located between the depths of 18-30 meters, all other areas are between 9 and 16 meters deep. The mean distance to the shoreline ranged from 14 to 38 km. The major fishing area is Risca with 109.5 km2 and the smallest is Molhe with 31.8 km2. All fishing areas are inserted on the bioclastic substrate. This type of sediment occurs from a depth of two to over 30 meters. The interviews showed that fishermen have a detailed knowledge about the substrate of fishing areas. In 2009 was caught 56506.9 kg of whole lobsters at Redonda‟ beach, with the highest production in the area called Cabeço. The fishermen prefer to fish in areas closer to the shore, but do not avoid going to the outer areas. The speed and wind direction influence the choice of fishing areas to be explored acting in the designation of spaces for resource exploitation. The currents and tides influence the production of lobster, and may occur alternations between more productive and less productive periods